Pengaruh Motivasi Kerja dan Budaya Organisasi Terhadap Efektivitas Kinerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Pemerintah Kota dan Kabupaten Malang - Ravy Radiyya Ajiwahyu; Ilfi Nur Diana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the variables that influence performance effectiveness and their influence on employees at the Personnel and Human Resources Development Agency of the Malang City and Regency Government. The type of research used is quantitative with a descriptive approach. Primary data in this study used a questionnaire which was distributed using a questionnaire sheet. The population in this study were employees of the Personnel and Human Resources Development Agency of the Malang City and Regency Government and a sample of 99 respondents. Using the Partial Least Square (PLS) analysis method 3. Based on the research results, it shows that the work motivation variable is not significant on the effectiveness of employee performance at the Personnel and Human Resources Development Agency of the Malang City Government. And the Organizational Culture variable is significant for the effectiveness of employee performance in the Malang City Government Personnel and Human Resources Development Agency employees. It can be concluded that this shows that the work motivation of employees of the Personnel and Human Resources Development Agency in Malang City and Regency has not been able to reduce the level of performance effectiveness. This shows that the better the organizational culture that exists among the employees of the Personnel and Human Resources Development Agency in Malang City and Regency, the lower the level of performance effectiveness.